Nutritional contribution of torula yeast and fish meal to the growth of shrimp Litopenaeus vannamei as indicated by natural nitrogen stable isotopes - Gamboa Delgado, Julián; Fernández Díaz, Benigno; Nieto López, Martha Guadalupe; Cruz Suárez, Lucía Elizabeth (B.A. Costa-Pierce, 2016)
Torula yeast (Candida utilis) and fish meal were used to formulate six experimental diets for Pacific white shrimp Litopenaeus vannamei. The dietary nitrogen supplied by fish meal was replaced by increasing dietary proportions of torula yeast (0, 7.5, 15, 30, 60 and 100%). Nitrogen stable isotope values (δ15N) were measured in ingredients, diets and muscle tissue of experimental animals in order to estimate the relative contributions of dietary nitrogen and dry matter supplied by both ingredients. At the end of a 29 d bioassay, there were no significant differences in survival rate among treatments. Shrimps fed on all diets containing torula yeast and fish meal had higher growth rates (k = 0.059-0.064) than animals fed on diets containing only fish meal or only torula yeast (k = 0.041-0.054). Incorporation of δ15N values of ingredients and muscle tissue into an isotopic mixing model indicated that the relative incorporation of dietary nitrogen and total dry matter from torula yeast to growth consistently increased in relation to increasing proportions of this ingredient in the experimental diets. The only exception was the diet formulated with the highest yeast content (60%, diet 40F/60T) where fish meal contributed a higher proportion of dietary nitrogen to growth. Dietary nitrogen from torula yeast available in diets 93F/7T, 85F/15T, 70F/30T and 40F/60T was incorporated in muscle tissue at proportions of 6.5, 13.7, 27.1 and 50.5 %, respectively. Estimated nitrogen residency time in tissue (t50) was relatively shorter in shrimps fed on diets 85F/15T and 70F/30T (3 d), indicating higher metabolic turnover rates in these animals than those fed on diet containing only fish meal. Growth and survival rates were statistically similar in shrimp fed on all mixed diets, therefore indicating the suitability of this single cell protein as dietary ingredient in diets containing up to 60% of torula yeast.